2020
DOI: 10.1101/2020.12.10.418996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Betulonic acid derivatives inhibiting coronavirus replication in cell culture via the nsp15 endoribonuclease

Abstract: The lack of medication to suppress coronavirus infections is a main reason for the dramatic course of the COVID-19 pandemic. There is an urgent need to identify suitable coronavirus drug targets and corresponding lead molecules. Here we describe the discovery of a class of coronavirus inhibitors acting on nsp15, a hexameric protein component of the viral replication-transcription complexes, endowed with immune evasion-associated endoribonuclease activity. SAR exploration of these 1,2,3-triazolo fused betulonic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Next, a pocket-selection tool (Qvina-W for blind docking [29]) was used to identify the most likely ligand binding pockets in the C-terminal catalytic domain surrounded by His235 and His250 in the nsp15 monomer. This approach is consistent with previous studies where a similar region was used for the nsp15 docking calculations [16]. Using Exebryl-1 and the identified pockets, docking scores were generated.…”
Section: Native Mass Spectrometry (Ms) and Molecular Docking Of Nsp15supporting
confidence: 53%
See 2 more Smart Citations
“…Next, a pocket-selection tool (Qvina-W for blind docking [29]) was used to identify the most likely ligand binding pockets in the C-terminal catalytic domain surrounded by His235 and His250 in the nsp15 monomer. This approach is consistent with previous studies where a similar region was used for the nsp15 docking calculations [16]. Using Exebryl-1 and the identified pockets, docking scores were generated.…”
Section: Native Mass Spectrometry (Ms) and Molecular Docking Of Nsp15supporting
confidence: 53%
“…Indeed, the intermolecular bonds of the hexamer appear to stabilize the active site of nsp15 endoU. A recent preprint demonstrates nsp15 function in alpha coronavirus isolate, HCoV-229E, and chemical-genetic validation with a betulonic acid derivative (lead molecule 5h) that inhibited replication of Coronavirus 229E at 0.6 µM EC50 [16]. It was shown that a nsp15 deficient coronavirus was much less sensitive to 5h and selecting for mutants with 5h led to mutations in the N terminus of nsp15 that map to residues important in the hexameric macromolecule of CoV nsp15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present result suggests that in addition to the enzyme active center, the multimer interface may become a good target of inhibition. Indeed, a recent preprint article [26] has reported that Betulonic acid derivatives can inhibit nsp15 via the binding to multimer interface site. The development of a systematic screening procedure targeting these multimer interfaces may be beneficial to stand against different pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Natural and semisynthetic tetra-and pentacyclic triterpenoids (compounds 225-234 [57,90,[151][152][153][154][155]) were found capable of inhibiting SARS-CoV-2 replication (Fig. 25 Natural and semisynthetic antibiotics 235-240 [57,85,90,156,157] showed quite a high in vitro activity aganst coronaviruses.…”
Section: Doi: 101134/s107042802105002xmentioning
confidence: 99%